2017
DOI: 10.1007/s11906-017-0797-z
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenases and Hypertension in the Metabolic Syndrome

Abstract: The metabolic syndrome describes a clustering of risk factors—visceral obesity, dyslipidaemia, insulin resistance, and salt-sensitive hypertension—that increases mortality related to cardiovascular disease, type 2 diabetes, cancer, and non-alcoholic fatty liver disease. The prevalence of these concurrent comorbidities is ~ 25–30% worldwide, and metabolic syndrome therefore presents a significant global public health burden. Evidence from clinical and preclinical studies indicates that glucocorticoid excess is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…The failure of neural and hormonal regulatory systems to adapt to high dietary salt intake is an important contributing factor to salt-sensitivity. In this context, sustained glucocorticoid excess, whether overt in Cushing’s or covert in Metabolic Syndrome, induces salt-sensitive hypertension and increases cardiovascular risk ( Bailey, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of neural and hormonal regulatory systems to adapt to high dietary salt intake is an important contributing factor to salt-sensitivity. In this context, sustained glucocorticoid excess, whether overt in Cushing’s or covert in Metabolic Syndrome, induces salt-sensitive hypertension and increases cardiovascular risk ( Bailey, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve aldosterone-dependent response, the MR is protected from plasma glucocorticoid excess by corticosteroid 11-beta-dehydrogenase isozyme 2/11β-hydroxysteroid dehydrogenase 2 (11β-HSD2) enzyme that converts cortisol to inactive cortisone. Action of 11ß-HSD2 creates glucocorticoid-free environment locally and makes MR action finely attuned to aldosterone concentration [15]. The role of aldosterone-MR complex in regulating homeostasis is mostly opposite to that of atrial natriuretic peptide (ANP) secreted by the heart.…”
Section: Mineralocorticoid-dependent Regulation Of Bpmentioning
confidence: 99%
“…In turn, 11β-HSD2 is involved in carcinogenesis, tumor progression and metastasis along with its role in inflammation and hypertension regulation [ 18 , 19 ]. There are studies that have shown the promotion of tumor progression and metastasis by this enzyme, which may be due to its physiological function of inactivating glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%